A STUDY OF INVESTORS’ PSYCHOLOGY WITH RESPECT TO MUTUAL FUNDS - Mahamuni, Pravin Narayan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Mutual Funds today are one of the most studied areas in developed countries due to their efficient and effective role in reducing risk and enhancing return through professional management of funds. These funds boost the incomes of small investors as well as reduce their exposure to unsystematic risks which needs to be taken into consideration for accurate results. The funds have become extremely popular over the last 20 years. The same funds which were once an obscure instrument are now part of daily lives. Therefore, the main focus of this research paper is to identify the investors’ psychology towards investment decision in mutual funds. The sample size for the study was 200 investors in Pune (100 respondents) & Satara District in India (100 respondents).